Drug-targeted endoscopic submucosal dissection: a hypothetical framework toward non-electromechanical mucosal resection - Song, Conghua; Xu, Huiyuan; Li, Xiaomei (Frontiers in Medicine, 2025)
Endoscopic submucosal dissection (ESD) is a widely used technique for en bloc resection of gastrointestinal neoplasms. However, it is technically demanding, time-consuming, and associated with risks such as perforation and bleeding, primarily due to the reliance on electromechanical dissection. In this theoretical proposal, we introduce a novel concept termed “drug-targeted endoscopic submucosal dissection (DT-ESD),” which aims to partially replace mechanical dissection by localized chemical degradation of the submucosa. The proposed method preserves most procedural steps of conventional ESD but incorporates selective enzymatic digestion to facilitate submucosal separation. This approach has the potential to reduce procedure time, thermal injury, and technical complexity. We detail the conceptual workflow, candidate agents, delivery strategy, potential advantages, and risks. Though theoretical at this stage, DT-ESD represents a potential paradigm shift in endoscopic therapy. Further validation in ex vivo and in vivo models is needed. If validated, DT-ESD could transform the paradigm of minimally invasive gastrointestinal therapy and could represent a transformative advancement in therapeutic endoscopy.